POTENSI LIMBAH PASAR SAYUR MENJADI STARTER FERMENTASI - CS. Utama; A. Mulyanto (JURNAL KESEHATAN, 2009)
Abstract Waste of vegetable market is solid waste organic consist of set of many vegetable after sorted because has been competent sell. Waste of vegetable rnarket in general predominated by cabbage and mustard. Cabbage production in Kabupaten Semarang according to BPS Kabupaten Semarang (2006) in number in 2005 reach 96.906 kws, whereqs mustard reaches 78,911 h,ys. Base perception at the site, mustord qnd exterior cabbage are thrown awqy counted j-5oh from heavy fresh vegetable because its condition improper sells. Waste of vegetable market haves big enough potency far exploited see enough to the number of mustard qmount and cabbage are thrown away. 600% wqste that indigenous to commercial activity in mqrket have the shape of vegetqbles waste and 20o% its hqve the shope of fruits garbage. According to Badan Pusat Statistik, in Central Java there is 1976 market units that produce market waste 1.300.000 tons every day in the form offresh, and a large part of (60%o) is organic garbage waste that have weakness level ofhigh water as high as 92,44% easy causative of cabbage waste decays until needed quick to process wqste is referred cts. Processing that felt eficient, easy, cheap, environmentally friendly and produce addition earnings is by make ferment starter that comprising active milcroorganisme genuiness from materials referred as Keyword : fermentation, starter, waste, sauerkraut